THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE JOB SATISFACTION AT PT PRIMAS MULIA ABADI - Lauren Valencia; Jumriah Basri (Universitas Ichsan Sidenreng Rappang, 2025)
This study examines the impact of leadership styles on employee satisfaction at PT Primas Mulia Abadi. Leadership style is a crucial component in creating a positive work environment and encouraging employees to exhibit higher levels of productivity. This study employed a quantitative, descriptive, and verification approach. Data were obtained through questionnaires distributed to fifty permanent employees. The influence of leadership style on job satisfaction was measured through simple linear regression analysis. The results of this study indicate that leadership style has a positive and significant effect on employee satisfaction. The better the leadership style implemented in the company, the higher the level of employee satisfaction.